Evaluation of dosimetry and excess seeds in permanent brachytherapy using a modified hybrid method: a single-institution experience - Kobayashi, Kana (Oxford University Press, 2013)
Permanent prostate brachytherapy is frequently performed worldwide, and many studies have demonstrated its favorable outcomes. Implant seeds used in this procedure contain a precise amount of radionuclide and are completely sealed. Because these seeds are not manufactured in Japan, they are expensive (6300 yen per seed) and therefore need careful management as a radioisotope. The proper implantation technique requires considerable procedure time, good dosimetric outcomes and simple radioactive isotope management. To evaluate the modified hybrid interactive technique based on these considerations, we assessed 313 patients who underwent hybrid interactive brachytherapy without additional external beam radiotherapy. We evaluated the duration of the procedure, dosimetric factors and the total number of excess seeds. The dosimetric results from computed tomography on Day 30 of follow-up were: 172 Gy (range 130–194 Gy) for pD90, 97.8% (83.5–100%) for pV100, 54.6% (27.5–82.4%) for pV150, 164 Gy (120–220 Gy) for uD90, 194 Gy (126–245 Gy) for uD30, 210 Gy (156–290 Gy) for uD5, 0.02 ml (0–1.2 ml) for rV100 and 0 ml (0–0.2 ml) for rV150. The number of excess seeds was determined by subtracting the number of implanted seeds from the expected number of seeds calculated from previously proposed nomograms. As per our method, nine excess seeds were used for two patients, whereas using the nomograms, the number of excess seeds was approximately eight per patient. Our modified hybrid interactive technique reduced the number of excess seeds while maintaining treatment quality.